2008
DOI: 10.1074/jbc.m800190200
|View full text |Cite
|
Sign up to set email alerts
|

The Foxc2 Transcription Factor Regulates Angiogenesis via Induction of Integrin β3 Expression

Abstract: Forkhead transcription factor Foxc2 is an essential regulator of the cardiovascular system in development and disease. However, the cellular and molecular functions of Foxc2 in vascular endothelial cells are still not fully understood. Here, through gene expression profiling in endothelial cells, we identified molecules associated with cell-extracellular matrix interactions, integrin ␤3 (Itgb3), integrin ␤5 (Itgb5), and fibronectin, as downstream targets of Foxc2. We found that Itgb3 expression is directly reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 41 publications
3
62
0
Order By: Relevance
“…Among candidate molecules, the integrin subunit β3 (encoded by ITGB3) was previously shown to promote angiogenesis (Davis and Senger, 2005;Hayashi et al, 2008). In agreement, the present analyses showed a significant upregulation of ITGB3 in JunBoverexpressing ECs (Fig.…”
Section: Correlations Of Ec Gene Regulation With Junb Overexpression supporting
confidence: 79%
See 1 more Smart Citation
“…Among candidate molecules, the integrin subunit β3 (encoded by ITGB3) was previously shown to promote angiogenesis (Davis and Senger, 2005;Hayashi et al, 2008). In agreement, the present analyses showed a significant upregulation of ITGB3 in JunBoverexpressing ECs (Fig.…”
Section: Correlations Of Ec Gene Regulation With Junb Overexpression supporting
confidence: 79%
“…1G), potentially offering synergenic contributions to arterial differentiation and angiogenesis. Furthermore, ITGB3, which encodes the β3 subunit of integrin αVβ3 and is known to be involved in angiogenesis (Davis and Senger, 2005;Hayashi et al, 2008), was also significantly upregulated (Fig. 1G).…”
Section: Neurovascular Interactions In Developing Embryonic Mouse Limmentioning
confidence: 94%
“…Previous studies suggested several FOXC2 target genes in blood vascular endothelium based on computational analysis of proximal promoters (Hayashi and Kume, 2008a,b;Hayashi et al, 2008). In this report, we have studied the association of FOXC2 across the entire genome, and we show that the vast majority of FOXC2-binding sites are located in the intergenic and intronic regions, arguing that FOXC2 acts primarily via distal enhancers as previously observed for estrogen-related receptor  and FOXa1 (Carroll et al, 2005;Lupien et al, 2008).…”
Section: In Situ Hybridizationmentioning
confidence: 69%
“…Fibronectin-integrin interactions play an important role in cell adhesion, migration and invasion by activating integrin-linked signaling [24]. Hayashi et al [25] reported that FOXC2 induces the expression of the integrin β3 subunit by directly binding to the ITGB3 promoter, thereby regulating integrin β3-mediated endothelial cell adhesion and migration. In our study, we found that FOXC2 mediates FOXF2-regulated integrin β3 expression and cellfibronectin adhesion in BLBC cells, suggesting that integrin β3 is regulated by the FOXF2/FOXC2 pathway and contributes to the acquisition of the aggressive properties of BLBC cells.…”
Section: Discussionmentioning
confidence: 99%